The Effect of Surfactant Concentration on the Rate of CO2 Absorption by Carbonate Solution in Packed Tower - Fadil H. Faraj; Alyaa K. Mageed (Engineering and Technology Journal, 2009)
Absorption of carbon dioxide from gaseous mixture (carbon dioxide, air) wasstudied by using Carbonate Solution (Na2CO3) in a counter-current packed column (7.5 cmid, 1.70 m height), packed with glass rashing rings of 1.8 cm i.d to a depth of 1.1 m.The effect of Surfactant concentration (dodecyl benzene sulfuric acid sodium(DBS))(0.5, 1.5, 2.5gm/lit.), gas mass flux (0.05, 0.075, 0.1 kg/m2.sec) and liquid mass flux(kg/m2.sec) on the absorption rate of carbon dioxide and mass transfer coefficient wasstudied at constant carbonate concentration (0.3 kmol/m3), inlet carbon dioxideconcentration(0.08, Y2=0.086 mol CO2/mol air), ambient temperature and atmosphericpressure. The results show that the absorption rate tends to increase with increasing gas andliquid flow rate. Mass transfer coefficient (KG.a) increases with increasing liquid flow rateand slightly change with increasing gas flow rate. Increasing surfactant concentration(decreasing surface tension) leads to decrease the absorption rate and mass transfercoefficient.